Autonomic nervous system functions in childhood essential hypertension - Yakinci, C; Mungen, B; Tayfun, M; Gunduz, M; Karabiber, H (Blackwell Science, 1996)
The etiopathology of essential hypertension (EH) is still controversial, different pathologic mechanisms have been estimated as a cause of EH. One of these mechanisms is autonomic nervous system dysfunction (ANSD). Although there are different studies showing ANSD in adult EH, limited studies on ANSD in childhood EH are present. The present study was planned to investigate the role of ANSD in childhood EH. The study group (SG) consisted of 24 children with EH and the control group (CG) was 24 healthy children. Non-invasive autonomic nervous system function tests: the orthostatic test, Valsalva ratio, 30/15 ratio and heart rate responses to deep breathing were performed on members of both groups. The mean differences in systolic blood pressure between supine resting and standing positions in the study and control groups were significant (z = -2.577, P = 0.0051). The mean differences in diastolic blood pressure between supine resting and standing positions in SG and CG were found to be statistically meaningful (z = -2.722, P = 0.0033). The mean differences in heart rate variation during hyperventilation in SG and CG were significant (z = -2.54, P = 0.0055). The mean differences in the Valsalva ratio between SG and CG were not statistically meaningful (z = 1.52, P = 0.0643). The mean differences in the 30/15 ratio in SG and CG were not found to be significant (z = -1.455, P = 0.0735). In the light of these results, both sympathetic and parasympathetic autonomic nervous system dysfunction in childhood essential hypertension were found.
Keywords: autonomic nervous system; childhood; essential hypertension